Pak2 Regulates Hematopoietic Progenitor Cell Proliferation, Survival, and Differentiation. (23rd April 2015) - Zeng, Yi; Broxmeyer, Hal E.; Staser, Karl; Chitteti, Brahmananda Reddy; Park, Su-Jung; Hahn, Seongmin; Cooper, Scott; Sun, Zejin; Jiang, Li; Yang, XianLin; Yuan, Jin; Kosoff, Rachelle; et al.
Abstract: p21-Activated kinase 2 (Pak2), a serine/threonine kinase, has been previously shown to be essential for hematopoietic stem cell (HSC) engraftment. However, Pak2 modulation of long-term hematopoiesis and lineage commitment remain unreported. Using a conditional Pak2 knockout mouse model, we found that disruption of Pak2 in HSCs induced profound leukopenia and a mild macrocytic anemia. Although loss of Pak2 in HSCs leads to less efficient short- and long-term competitive hematopoiesis than wild-type cells, it does not affect HSC self-renewal per se. Pak2 disruption decreased the survival and proliferation of multicytokine stimulated immature progenitors. Loss of Pak2 skewed lineage differentiation toward granulocytopoiesis and monocytopoiesis in mice as evidenced by (a) a three- to sixfold increase in the percentage of peripheral blood granulocytes and a significant increase in the percentage of granulocyte-monocyte progenitors in mice transplanted with Pak2-disrupted bone marrow (BM); (b) Pak2- disrupted BM and c-kit + cells yielded higher numbers of more mature subsets of granulocyte-monocyte colonies and polymorphonuclear neutrophils, respectively, when cultured in the presence of granulocyte-macrophage colony-stimulating factor. Pak2 disruption resulted, respectively, in decreased and increased gene expression of transcription factors JunB and c-Myc, which may suggest underlying mechanisms by which Pak2 regulates granulocyte-monocyte lineage commitment. Furthermore, Pak2 disruption led to (a) higher percentage of CD4 + CD8 + double positive T cells and lower percentages of CD4 + CD8 − or CD4 − CD8 + single positive T cells in thymus and (b) decreased numbers of mature B cells and increased numbers of Pre-Pro B cells in BM, suggesting defects in lymphopoiesis. Stem Cells 2015;33:1630–1641